DIMENSI PENGALAMAN MISTIK (MYSTICAL EXPERIENCE) DAN CIRI-CIRINYA - Mr Muzairi (UIN Sunan Kalijaga Yogyakarta, 2014)
There seem to be two ways to discover the nature of religious experience. One way is to appropriate the historical formulation of one religion, denomination, or school of religious thought. Another way is to start from mystical experience or Sufism.Such is the case with Sufism, the generally accepted name for Islamic mysticism. To approach its partial meaning we have to ask ourselves first, what mysticism means. That mysticism contains something mysterious, not to be reached by ordinar y means or by intellectual effort, is understood from the root common to the words mystic and myster y, the Greek myein, “to close the eyes”. Mysticism has been called “the great spiritual current which goes through all religions”. In its widest sense it may be defined as the consciousness of the One Reality – be it called Wisdom, Light, Love or Nothing.